Torsion del cordón espermático. - Corral Rosillo, J.; Resel, Luis; Gómez Ruiz, J.J.; Gómez Vegas, Ángel; Silmi Moyano, A.; Blázquez Izquierdo, J. (Clínicas Urológicas de la Complutense, 1992)
Sin resumen